Sequencing batch reactor technology for landfill leachate treatment: A state-of-the-art review. (15th March 2021) - Jagaba, A.H.; Kutty, S.R.M.; Lawal, I.M.; Abubakar, S.; Hassan, I.; Zubairu, I.; Umaru, I.; Abdurrasheed, A.S.; Adam, A.A.; Ghaleb, A.A.S.; Almahbashi, N.M.Y.; Al-dhawi, B.N.S.; et al.
Abstract: Landfill has become an underlying source of surface and groundwater pollution if not efficiently managed, due to the risk of leachate infiltration into to land and aquifers. The generated leachate is considered a serious environmental threat for the public health, because of the toxic and recalcitrant nature of its constituents. Thus, it must be collected and appropriately treated before being discharged into the environment. At present, there is no single unit process available for proper leachate treatment as conventional wastewater treatment processes cannot achieve a satisfactory level for degrading toxic substances present. Therefore, there is a growing interest in examination of different leachate treatment processes for maximum operational flexibility. Based on leachate characteristics, discharge requirements, technical possibilities, regulatory requirements and financial considerations, several techniques have been applied for its degradation, presenting varying degrees of efficiency. Therefore, this article presents a comprehensive review of existing research articles on the pros and cons of various leachate degradation methods. In line with environmental sustainability, the article stressed on the application and efficiency of sequencing batch reactor (SBR) system treating landfill leachate due to its operational flexibility, resistance to shock loads and high biomass retention. Contributions of integrated leachate treatment technologies with SBR were also discussed. The article further analyzed the effect of different adopted materials, processes, strategies and configurations on leachate treatment. Environmental and operational parameters that affect SBR system were critically discussed. It is believed that information contained in this review will increase readers fundamental knowledge, guide future researchers and be incorporated into future works on experimentally-based SBR studies for leachate treatment. Graphical abstract: Image 1 Highlights: Application and efficiency of SBR system in treating landfill leachate. Comprehensive review on the pros and cons of various leachate treatment methods. Contributions of integrated leachate treatment technologies with SBR. Effect of different materials, processes, strategies and configurations on leachate treatment. Effect of environmental and operational parameters on SBR system efficiency.